Serum uric acid is associated with incident hip fractures in women and men – Results from a large Austrian population-based cohort study. (June 2021) - Preyer, Oliver; Concin, Hans; Nagel, Gabriele; Zitt, Emanuel; Ulmer, Hanno; Brozek, Wolfgang
Highlights: High serum levels of uric acid were associated with the risk of hip fractures occurring at age 50 years and over. The risk association was stronger in men than in women. Hyperuricemia was associated with greater hip fracture risk in men but not women. Among covariates, high total cholesterol was associated with lower fracture risk. Abstract: Objectives: Serum markers that can be used to estimate the risk of bone fractures are rare, and findings for one candidate marker, uric acid, are heterogeneous. Our aim was to investigate the potential of serum uric acid (SUA) to predict hip fractures occurring in people aged 50 years and over. Study design: During a medical prevention program over the period 1985–2005 in Vorarlberg, baseline data were collected on SUA levels and covariates (age, BMI, blood pressure, smoking status, diabetes, triglycerides and cholesterol) from 185, 397 individuals, of whom 42, 488 women and 35, 908 men met the inclusion criteria of this population-based cohort study. Information on incident cancer and end-stage kidney disease was acquired from registries. Main outcome measure: Incident hip fracture occurring in participants aged 50 years and over during the observation period 2003–2013. Results: SUA was associated with a rise in female hip fracture risk by 6% per unit increase (HR 1.06, 95 %-CI 1.01−1.10), and risk in the highest vs. lowest SUA quartile was significantly increased (HR 1.17, 95 %-CI 1.01−1.35), but not at hyperuricemic (>5.7 mg/dl) vs. normouricemic (≤5.7 mg/dl) levels. In men, hip fracture risk rose by 15 % per unit increase (HR 1.15, 95 %-CI 1.08−1.22), and risk was significantly higher in the highest vs. lowest SUA quartile (HR 1.50, 95 %-CI 1.17−1.91) as well as at hyperuricemic (>7.0 mg/dl) vs. normouricemic (≤7.0 mg/dl) levels (HR 1.48, 95 %-CI 1.19−1.84). Conclusions: Our results link SUA with increased risk of hip fractures, particularly in men.